Audit Quality and the Financial Performance of Quoted Companies in Nigeria: Empirical Discourse - Jeroh, Edirin; Ozegbe, Kenneth Kaunda (Acta Universitatis Danubius. Œconomica, 2022)
This report presents the outcome of a research that examines audit quality attributes as possible determinants of companies’ financial performance. Specifically, the study drew inference from quoted companies in Nigeria, with data covering 10 years (2011 to 2020). The proxy for audit quality were statutory audit services, audit tenure, auditor’s independence, and audit-firm size; whereas, firm performance was measured by Return On Assets (ROA). Firm year data which were collated from their respective annual reports were obtained from the database of MACHAMERATIOS. The study adopted the Panel Least Square technique, descriptive analysis and relevant diagnostic tests as part of the tools used in analyzing the data collated. From the results, while we notice that audit independence exerts significant negative influence on ROA; audit tenure and audit firm size had positive relationship with ROA, although, this relationship was not significant. Conversely, statutory audit service on its own significantly influenced firm performance (ROA). Overall, measures of audt quality exert joint significant influence on ROA. With the study’s results, we recommend among others that the country’s Financial Reporting Council and other regulators should develop policy guidelines to specifically checkmate auditors’ tenure vis-à-vis compliance to existing regulatory framework for financial reporting.